2018
DOI: 10.4315/0362-028x.jfp-17-290
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heating Conditions for Inactivation of Hepatitis E Virus Genotypes 3 and 4

Abstract: Hepatitis E virus (HEV) is a causative agent of acute hepatitis throughout the world. HEV genotypes 1 through 4 infect humans, whereas genotypes 3 and 4 (Gt3 and Gt4) also infect other animals. In developed countries, the main HEV infection route is by foodborne transmission, resulting from the consumption of undercooked meat. It is important to know the criteria for HEV control in daily cooking. In this study, we assessed the heat conditions required to inactivate HEV Gt3 and Gt4 in culture supernatants and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Some differences have been recently reported by Imagawa et al (2018) who studied HEV inactivation by measuring virus replication in PLC/PRF/5 cell culture. The results showed that exposure to 65°C for 5 min or 75°C for 1 min inactivated HEV-3, while HEV-4 was inactivated at 80°C for 1 min.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Some differences have been recently reported by Imagawa et al (2018) who studied HEV inactivation by measuring virus replication in PLC/PRF/5 cell culture. The results showed that exposure to 65°C for 5 min or 75°C for 1 min inactivated HEV-3, while HEV-4 was inactivated at 80°C for 1 min.…”
Section: Resultsmentioning
confidence: 80%
“…Molecular methods, particularly real-time reverse transcriptase polymerase chain reaction (RT-qPCR), have demonstrated high sensitivity, specificity, and ability to deliver reliable quantitative data in food and environmental samples (Martin-Latil et al, 2014, 2016; Di Bartolo et al, 2015; Mesquita et al, 2016), although such results do not indicate at the infectivity of detected viruses. In addition, alternative strategies to directly study infectivity such as cell culture systems and animal models do not seem to be reliable or practical yet (Ricci et al, 2017; Van der Poel et al, 2018), although promising results have been reported (Emerson et al, 2005; Johne et al, 2016; Imagawa et al, 2018). To enable the differentiation between infectious and inactivated viral particles, different approaches based on capsid integrity have been reported:…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, pork is generally roasted before eating and dried sausages are rarely consumed raw. Barbequed pork could be undercooked; however, the infectious viral titer should be lower than that in figatelli or paté [ 36 , 37 , 38 ]. In interviews carried out at the hepatology Unit, only two patients in our study admitted to eating dried sausage.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, single, non-epidemic zoonotic HEV genotype 3 infections occur in Europe, North- and South America and Australia: contact with swine and consumption of inadequately heated pork are sources of infection with Genotype 3. Pork needs to be cooked for more than 5 min at 70 °C to inactivate the HEV virus [5]. Likewise, genotype 4 infections are also transmitted by pork, but this genotype is prevalent in Asia and only single rare cases have been described to be autochthonously acquired in Europe [6].…”
Section: Introductionmentioning
confidence: 99%